Development of nonlinear model for continuous stirred tank reactor (CSTR) - Mohamad Ikwan, Zakaria (2010)
Continuous stirred tank reactors (CSTR) finds wide application in the chemical industry from pilot plant to full-scale production operation.CSTRs generally present operational problems due to complex open-loop nonlinear behavior in the form of input/output multiplicities and ignition/extinction phenomena.A major limitation of linear model is that plant behavior is described by linear dynamic model.As a result,linear model is inadequate for highly nonlinear process and moderately nonlinear process which have large operating regimes.This shortcoming coupled with increasingly stringent demands on throughput and product quality has spurred the development of nonlinear model.The objective of this research are development mathematical model for CSTR process based on first principal,validation of mathematical model through experimentation and nonlinear model identification of a CSTR process.The mathematical model based on first principles is developed from sodium hydroxide,ethyl acetate,and sodium acetate and ethanol mass balance.Then,the model equation is solving in MATLAB environment by doing algorithm for this process.The program for CSTR system is created and this program known as nonlinear fundamental model.The result from the MATLAB simulation program is compared with experimental result to validate the fundamental model. As a conclusion,the suitable nonlinear model for CSTR system has been developed and analysis shown the compatibility of the model with experimental result.